2022
DOI: 10.5650/jos.ess21288
|View full text |Cite
|
Sign up to set email alerts
|

Anti-human Glioma Cancer Potentials of Neobavaisoflavone as Natural Antioxidant Compound and Its Inhibition Profiles for Acetylcholinesterase and Butyrylcholinesterase Enzymes with Molecular Modeling and Spin Density Distributions Studies

Abstract: IntroductionThe chemotherapeutic materials are a special type of drugs and supplements that are used to treat several types of cancers such as glioma cancer in human 1−3) . The present chemotherapeutic drugs/supplements have many side effects for body, so that mostly the patients die due to the side effects of the chemotherapeutic drugs/supplements instead of cancer 2−4) . It is important to design new chemotherapeutic medications due to the strong side effects of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…in PF were medium toxic. The IC 50 values were various to different cell lines and most of them ranged between 20 and 200 μg/ml ( Song et al, 2018 ; Guo et al, 2021 ; Chen et al, 2022 ). In this study, the total content of IBCL and 4MBCL in PFPE was 18.18%, other compounds (49.26%) mentioned above may have low cytotoxicity to Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…in PF were medium toxic. The IC 50 values were various to different cell lines and most of them ranged between 20 and 200 μg/ml ( Song et al, 2018 ; Guo et al, 2021 ; Chen et al, 2022 ). In this study, the total content of IBCL and 4MBCL in PFPE was 18.18%, other compounds (49.26%) mentioned above may have low cytotoxicity to Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As for corylifol C, it has been demonstrated to show significant anti‐bacterial activities against two pathogenic bacteria 61 . Neobavaisoflavone and isoneobavaisoflavone are natural anti‐oxidant compounds, which exhibited significant anti‐cancer potential against human glioma 62 . Therefore, the markers we obtained are all pharmacologically active and may affect the clinical efficacy of FP to some extent, which requires increasing attention in the quality control process.…”
Section: Resultsmentioning
confidence: 96%
“…The other pathways were related to anticancer and estrogen-like effects [ 11 , 25 , 26 ]. Besides the pharmacological mechanisms of anti-osteoporosis, anti-cancer, and estrogen-like effects, the pathways were also related to anti-inflammatory, antioxidant, neuroactive, and adrenergic effects [ 27 , 28 ]. In addition, the results of KEGG analysis also showed that neobavaisoflavone might interfere with lipid metabolism to produce toxicity through the steroid hormone biosynthesis pathway, which was consistent with the literature [ 14 ] that the neobavaisoflavone had certain hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%